Pendekatan Psikodinamika Untuk Pengembangan Kepemimpinan - Eka Beryl Safaat; Hanifah Nur Aqilah; Mochammad Isa Anshori (Jurnal of Management and Social Sciences, 2023)
This study aims to determine the Psychodynamic Approach in the context of leadership. The type of research used is a literature study. The data used in this study are secondary data obtained from literature reviews and websites related to the research topic. Conclusions are drawn by combining the results of previous studies with existing data and several literature references. The results of the research show that the psychodynamic approach in the study and development of leadership focuses on the dynamics of human behavior. Furthermore, the psychodynamic approach maintains the idea that psychological, social, and emotional processes between leaders and followers have a major influence. Keywords: Psychodynamic Approach, Leadership, Leadership Development